Penerapan Konsep Arsitektur Perilaku: Ruang Kelas Pondok Pesantren Al-Hidayah Kota Jambi - Komalasari, Liza; Tela, I Nengah (Jurnal TekstuReka, 2024)
Along with the pace of community development, Islamic boarding school education, both in terms of location, form and substance, has undergone many changes. Islamic boarding schools are no longer as simple as people describe them. Islamic boarding schools can experience changes according to the growth and development of the times. One of them is the khalafiyah or modern pesantren, which implements a classical teaching system by providing general knowledge and religious knowledge, as well as providing skills education. One of the Islamic boarding schools that use this education system is the Al Hidayah Islamic Boarding School in Jambi City. The considerations made are related to the behavior patterns of MI students which need to be reformed and improved for the progress of Islamic boarding schools by applying patterns that are appropriate to student behavior. This study aims to obtain a good arrangement of spatial patterns for students to learn. The method is done by taking a simple random sample or called simple random sampling. The results of the study provide recommendations for design patterns that can be applied in the interior space.